Globalization and the new realities in the Muslim world - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah (London Churchill College, 2021)
Long before the coming of the modern era of globalization from the West, the Muslim world had seen and enjoyed its own era of globalization. The Muslim era of globalization happened exactly during the peak of the Islamic civilization (750-1258). Around that era, there appeared a great multitude of Muslim scholars and scientists. The openness of the Islamic civilization led early Muslims scholars to borrow ideas from the earlier civilizations; like the Greeks, Persians and Indians. Many pioneering works produced by early Muslims scholars in the areas of science, technology and philosophy later immensely benefited scholars in the West. Concurrent to modern globalization was the era of European colonization of the East and Africa. Since then, Western globalization has been influencing every part of the globe. In the last few decades with the advent of the internet and now social media, knowledge and information sharing have become a lot easier than before. At times, however, the internet and social media have negatively impacted on the masses living in the East, nevertheless their positive impact challenges governments and local authorities in many countries to practice good governance in the day-to-day running of their countries. Through this paper, the researchers intend to explore globalization from the Islamic perspective and discuss issues related to the practice of good governance, politics and the phenomenon of brain drain in the Muslim world. As a qualitative study, this research employs the library research method that uses the textual and content analysis techniques. Pertinent data related to the study will be gathered from print and internet sources.